Mobile Wallet App: The determinants influencing consumers’ behavioural intention to use in restaurant - Mohd Saiful Jamil; Nurfatin Syafiqa Norman; Nor Jumaiza Aziz; Wee May Yee (2021)
This study was conducted to examine the determinants influencing consumers’ behavioral intention to use mobile wallet in restaurant. The independent variables of this study comprised mobile usefulness, mobile ease of use and mobile self-efficacy; whereas the dependent variables in this study was behavioral intention. This study had three objectives which was to examine the relationship between mobile usefulness and behavioral intention, to evaluate the relationship between mobile ease of use and behavioral intention and to investigate the relationship between mobile self-efficacy and behavioral intention. The quantitative research method was selected and questionnaire was used as the research instrument to collect the data. Convenience sampling method was used and 316 respondents were evaluated in this study. Structured questionnaire was used in this study. The data was collected using Google Form. The data collected was analyzed by using Statistical Packages for Social Science Version 26 (SPSS Version 26) software based on descriptive statistic, reliability analysis, and correlation analysis. As for the result, all the independent variables (mobile usefulness, mobile ease of use and mobile self-efficacy) that had been studied in this research had significant relationships towards dependent variable (behavioral intention) that used in restaurant. Through this study it would understand the determinants of influencing consumers’ behavioral intention and a better understanding and knowledge that affect mobile wallet users.